The Orchestra Nocturne: Description For Six New Katydid Species From India (Orthoptera: Tettigoniidae) - Tiwari, Chandranshu; Diwakar, Swati (Zootaxa, 2024)
The paper describes six new species from three genera of Tettigoniidae. The paper evaluates the status of Hexacentrus Serville 1831, Phyllomimus Stål 1873 and Euconocephalus Karny 1907. Diagnostic characters for new members of each genus are described along with additional information about the ecology and distribution of species. Keys to all species of each genus is presented. Of the six, three namely H. sylavanus sp. nov., E.helleri sp. nov and E. brevicornis are recorded only from Assam. One species, E.latipennis is recorded from Arunachal Pradesh and one species P.midoriyae is recorded from both locations. One species E. malabaricum is recorded from the Alappuzha district, in Kerala. The paper also demonstrates the importance of acoustic signals in taxonomic studies.